2013
DOI: 10.2478/auoc-2013-0006
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid and fat soluble vitamins composition of raw and cooked Black Sea horse mackerel

Abstract: Abstract. The fat soluble vitamins, as well as n3 and n6 fatty acids (FA) are essential compounds of fish lipids and exclusively provided by the diet. Fish is sometimes eaten raw, but it is usually thermal processed before consumption. Temperature processing of fish tissue enhances its taste, inactivates pathogenic microorganisms and increases its shelf life. The fat soluble vitamins (vitamins A, D 3 and E) and fatty acids are considered to be susceptible to oxidation during heating (cooking) process. The aim … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 14 publications
(28 reference statements)
4
18
0
Order By: Relevance
“…Ersoy and Özeren [ 61 ] reported a significant increase in tocopherol content in African catfish after different treatments such as baking, grilling, microwaving, and frying. Merdzhanova et al [ 60 ] also found a significant increase in tocopherol content after frying in Black Sea horse mackerel.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Ersoy and Özeren [ 61 ] reported a significant increase in tocopherol content in African catfish after different treatments such as baking, grilling, microwaving, and frying. Merdzhanova et al [ 60 ] also found a significant increase in tocopherol content after frying in Black Sea horse mackerel.…”
Section: Resultsmentioning
confidence: 95%
“…The α-tocopherol content ranged from 0.69 to 0.88 mg/100 g in raw eels. The vitamin E content in fish can differ widely between species and it is also affected by the season, genetic differences, tocopherols in feed, maturation stage, or storage conditions [ 4 , 60 ]. Additionally, vitamin E content in fish seems to be directly related to lipid content and n-3-PUFA content [ 4 ].…”
Section: Resultsmentioning
confidence: 99%
“…Merdzhanova et al. (2013) observed that the vitamin E content of Black Sea horse mackerel increased significantly after frying. However, Gotoh et al.…”
Section: Resultsmentioning
confidence: 99%
“…No previous studies have investigated the effect of all steps of the fish canning process on vitamin content, and we were only able to find data on the effect of some heat treatments. Merdzhanova et al (2013) observed an increase in vitamin A content in horse mackerel fillets fried in sunflower oil and a decrease in the same after the sterilization process.…”
Section: Fat-soluble Vitaminsmentioning
confidence: 88%
See 1 more Smart Citation